BERBAGAI UPAYA PENCEGAHAN COVID-19 - Afrianto, Yuggo; Ginting, Novita Br; Indriyawati, Indriyawati; Dewi, Kalih Puspita; Fahrezi, Muhamad Rizky (Universitas Tarumanagara, 2021)
Covid-19 is a new type of virus that was discovered in Wuhan, Hubei, China, in 2019. The new kind of virus was given the name coronavirus disease-2019, shortened to Covid-19. WHO declared this virus a pandemic on March 11, 2020. Various parties tried to in the prevention and control of COVID-19. However, the number of references offered and the variance of a policy in a study create problems again. People are confused to understand what efforts are suitable or recommended with trustworthy truths. Hence, this study uses Systematic Literature Reviews to find the most recommended efforts with reliable study sources, namely the Scopus journal and Google Scholar. The results of this study provide recommendations to the public about the efforts to prevent Covid-19, to reduce the spread of Covid-19, especially in Indonesia. 125 relevant journals were successfully reviewed, resulting in 37 Covid-19 prevention efforts. Based on the ranking method, 10 efforts are widely recommended in journals, namely: Social distancing, Quarantine/lockdown/LSSR (Large-scale social restrictions), WFH (Work From Home), Washing hands, Self-isolation, Wearing masks, Using handsanitizer, Spraying disinfectants, Maintaining immunity, and Not touch the face. The exciting thing that was also found in the research was that there were efforts that were not only built based on medical science but were also associated with beliefs such as Sawen Installation and Religious Ceremonies. Keywords: Covid-19; SLR; prevention of Covid-19. AbstrakCovid-19 merupakan virus jenis baru yang ditemukan di Wuhan, Hubei, China pada tahun 2019, virus ini diberi nama corona virus disease-2019 yang disingkat menjadi Covid-19, WHO (World Health Organization) menyatakan virus ini sebagai suatu pandemi pada 11 Maret 2020. Berbagai pihak berupaya dalam pencegahan dan penanggulangan Covid-19. Namun banyaknya referensi yang ditawarkan dan ketidak selarasan suatu kebijakkan dalam suatu studi, membuat permasalahan kembali di mana masyarakat bingung untuk mengerti upaya apa saja yang baik atau direkomendasikan dengan kebenaran yang dapat dipercaya. Untuk menangani masalah tersebut maka dalam penelitian ini menggunakan Systematic Literature Reviews untuk mencari upaya yang paling banyak direkomendasikan dengan sumber studi yang terpercaya, yaitu jurnal Scopus dan Google Scholar. Hasil penelitian ini memberikan rekomendasi kepada masyarakat tentang apa saja upaya pencegahan Covid-19, untuk mengurangi penyebaran Covid-19 khususnya di Indonesia. 125 jurnal yang relevan berhasil direview, menghasilkan 37 Upaya pencegahan Covid-19. Berdasarkan metode pemeringkatan mendapatkan 10 upaya yang banyak direkomendasi dalam jurnal, yaitu: Social distancing, Karantina/lockdown/PSBB (Pembatasan Sosial Berskala Besar), WFH (Work From Home), Mencuci tangan, Isolasi diri, Memakai masker, Memakai handsanitizer, Menyemprotkan disenfektan, Menjaga imun, dan Tidak menyentuh wajah. Hal menarik yang didapatkan juga dalam penelitian ternyata terdapat upaya yang tidak hanya dibangun berdasarkan ilmu medis, namun juga dikaitkan dengan kepercayaan seperti, Pemasangan Sawen dan Upacara Keagamaan.